Hedonic Benefit Perceptions, Brand Image, and Consumer Happiness in Smartphone Purchases - Sunay, Melda Medine; Tabanlı, Seda Muti (Ebru Bagci, 2025)
Today, the purchasing processes of technology products are shaped not only by functional utility but also by emotional and hedonic motivations. In the current age of consumption, many emotional purchasing experiences have shown that consumption is not based on rational decisions alone but is based on pleasure. Particularly in high-involvement products like smartphones, consumers associate happiness not just with technical features but also with experiential values (prestige, entertainment, aesthetics) offered by the product. However, multidisciplinary studies on how brand image mediates this relationship remain limited. The aim of this study was to determine the effect of hedonic value perception on consumer happiness and the mediating role of brand image in the smartphone preferences of consumers. The study was conducted with 396 participants living in Bursa. The convenience samp ling method was used within the non-probability sampling design, and data were collected using an online questionnaire. Simple Linear Regression was used in the analysis of the study hypotheses, and to test the hypothesis related to the mediating effect, Process Macro (Model 4), developed by Hayes, was applied. The findings obtained in the study demonstrated that the hedonic benefit perception had a positive effect on consumer happiness. Brand image was also found to have a mediating effect between hedonic benefit and consumer happiness. © 2025, Ebru Bagci. All rights reserved.
Keywords: Emotional Value; Marketing Happiness; Smartphone Marketing; Statement of identity; Symbolic Consumption